2020
DOI: 10.1073/pnas.1912375117
|View full text |Cite
|
Sign up to set email alerts
|

DBC1, p300, HDAC3, and Siah1 coordinately regulate ELL stability and function for expression of its target genes

Abstract: Among all of the Super Elongation Complex (SEC) components, ELL1 (also known as ELL) is the only bona fide elongation factor that directly stimulates transcription elongation by RNA polymerase II. However, the mechanism(s) of functional regulation of ELL1 (referred to as ELL hereafter), through its stabilization, is completely unknown. Here, we report a function of human DBC1 in regulating ELL stability involving HDAC3, p300, and Siah1. Mechanistically, we show that p300-mediated site-specific acetylation incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In cells, the levels of active SEC are modulated by targeted degradation of the AFF4 scaffold and ELL1/2 subunits by the E3 ubiquitin ligase SIAH1 (52)(53)(54)(55). Consistent with this, depletion of SIAH1 in MRC5 cells resulted in strongly (ϳ5-fold) enhanced levels of AFF4 protein and a concomitant increase in transcription of HSV IE (ICP4 and ICP27) genes (Fig.…”
Section: Suppression Of Hsv Ie Gene Expression and Lytic Infection By Inhibition Of The Secsupporting
confidence: 66%
“…In cells, the levels of active SEC are modulated by targeted degradation of the AFF4 scaffold and ELL1/2 subunits by the E3 ubiquitin ligase SIAH1 (52)(53)(54)(55). Consistent with this, depletion of SIAH1 in MRC5 cells resulted in strongly (ϳ5-fold) enhanced levels of AFF4 protein and a concomitant increase in transcription of HSV IE (ICP4 and ICP27) genes (Fig.…”
Section: Suppression Of Hsv Ie Gene Expression and Lytic Infection By Inhibition Of The Secsupporting
confidence: 66%
“…Lysine acetylation of non-histone proteins competes with ubiquitination to affect protein stability [ 9 ], and therefore we next examined the effect of SIRT2 expression on PARP1 levels. We found that increasing levels of SIRT2 overexpression led to a gradual reduction in PARP1 levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that PARP1 as the major factor in oxidative stress-induced cardiovascular injury undergoes ubiquitination by E3 ubiquitin ligase WW domain-containing protein 2 (WWP2) [ 6 , 7 ]. However, lysine deacetylation of non-histone proteins promotes ubiquitination to affect protein stability [ 9 ]. Deacetylation of PARP1, the regulatory mechanisms of PARP1 deacetylation, and the crosstalk of PARP1 post-translational modifications remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This makes sense, as CCAR proteins interact with steroid hormone receptors (Wu et al 2014). Additional studies with CCAR2 RNAi performed in HEK 293 human embryonic kidney cells confirmed the involvement of CCAR2 in regulating genes involved in metabolism (Basu et al 2020;Close et al 2012).…”
Section: Introductionmentioning
confidence: 92%